الشهادة على أثبات النسب في الفقه الإسلامي (Comprehensive Journal of Science, 2025)
This research examines the topic of testimony in establishing lineage (nasab) in Islamic jurisprudence, considering it one of the most important means of affirming rights—especially lineage, which Islamic law highly values as one of the five necessities and a key objective in preserving progeny. The study highlights the significance of lineage in Islam, its connection to family and society, and the material and moral rights it guarantees to the child, parents, family, and community, as well as its status as a public right. It also addresses the linguistic and legal definitions of testimony, its legitimacy in the Qur’an, Sunnah, and scholarly consensus, and explains its rulings, pillars, conditions of bearing and delivering testimony, and the required number of witnesses in lineage cases, along with the juristic views regarding the acceptance of male and female testimony.The research further explores the concept of evidence linguistically and technically, and identifies who has the right to claim lineage, clarifying that lineage is a right for the child, the mother, the father, society, and a right of God due to its implications for inheritance, maintenance, custody, guardianship, and preventing the mixing of lineages. It also reviews the key methods of proving lineage in Islamic law—marital bed (firaash), birth, and acknowledgment—and outlines the rules governing each. The study concludes that testimony is a foundational means of establishing rights, and that Islamic law has established a precise system to protect lineage from alteration or loss and prohibited anything that leads to its confusion, thereby preserving human dignity, family stability, and social order.
Keywords: Testimony – Lineage Establishment – Islamic Jurisprudence – Evidence Methods – Preservation of Lineage